Geografia, Patrimônio e Turismo na Amazônia Brasileira: o Projeto Roteiros Geo-Turísticos em Belém do Pará - Maria Goretti da Costa Tavares (Confins)
The formation of the city's heritage reveals itself, then, as a synthesis of the history and geography of the place, showing different forms of space appropriation. By revealing an opportunity to explore historical information through events and buildings over time, the Federal University of Pará, through the Faculty of Geography of the Federal University of Pará, specifically, the Research Study Group in Geography of Tourism (GGEOTUR) launched, on January 12, 2011, the project “Geo-tourist routes: getting to know the cultural heritage in Belém do Pará”. The project was born as a university extension activity, created with the aim of presenting to the scientific community, local society and tourists something that differs from a conventional tourist itinerary, seeking to combine historical, architectural, cultural and geographical knowledge. He inserts places that have not been frequently included in commercialized tours, spaces in which there is a clear lack of public power actions, especially with regard to cleanliness and safety, contrary to what occurs in certain restored and refunctionalized spaces. The intention is to provide society with heritage knowledge about the city of Belém, which is little revealed in actions by public authorities in general. The project aims to develop knowledge and theoretical and practical foundations for the elaboration of geo-tourist routes, based on the historical and spatial formation in the city of Belém. there they live. It is also proposed to present the geo-tourist routes to society and the public power as one of the perspectives of economic activities aimed at local development. This article presents the design, methodology and impacts of the project in the city of Belém do Pará.